Advances in atomic and molecular physics. Volume 19 - Bates, David R. (David Robert), 1916-1994.; Bederson, Benjamin; ScienceDirect eBooks (New York : Academic Press, 1983)
ADV IN ATOMIC & amp; MOLECULAR PHYSICS V19.
VI. Summary of Detailed Scattering Experiments and Concluding RemarksReferences; Chapter 8. Spin Polarization of Atomic and Molecular Photoelectrons; I. Introduction; II. Theory of Spin Polarization Phenomena in Atoms; III. Comparison with Experiment and Applications; IV. Spin Polarization of Molecular Photoelectrons; V. Conclusion; References; Index; Contents of Previous Volumes.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Molecules; Atoms; SCIENCE -- Physics -- Quantum Theory; Atoms; Molecules; Electronic books